«Seigneurial Pervasiveness» at the End of the Middle Ages. Notes on a Recent Research Project (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
This paper provides an insight into a recently funded research project on rural lordship in Italy at the end of the Middle Ages. To this end it highlights first and foremost the relevance of this topic, which has been largely overlooked by earlier scholarship. Then it focuses on the scientific approach, describes the research units involved, and explains the proposed methodology.Keywords: Stato; signoria rurale; Medioevo; feudo; potere. State; rural lordship; Middle Ages; fief; power.DOI 10.17464/9788867742776
Keywords: State; rural lordship; Middle Ages; fief; power